A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) from Italy - Bernardo, Umberto; Gualtieri, Liberata; Nugnes, Francesco; Verdolini, Elisa; Riolo, Paola; Viggiani, Gennaro (Zootaxa, 2017)
A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) that emerged mostly from galls induced by Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae) on chestnut is described from Italy. The characterization of the new taxon, Soikiella italica Viggiani sp. n., was performed through a morpho-molecular approach. A key to the species of Soikiella is given. Emerging from the same samples were a few females of an unidentified species of Trichogramma Westwood that likely emerged from eggs of Lepidoptera associated with the galls. The true host of S. italica is also indicated to be the eggs of some insect other than D. kuriphilus that uses their galls as oviposition sites.